Greg Weight interviewed by Frank Heimans - Weight, Greg, 1946-; Heimans, Frank, 1943- (2000)
Weight speaks about his reasons why he was attracted to photography and the importance of establishing himself as a freelance photographer; elaborates on the development of his work in commercial photography and fashion during the 1960s. He speaks of his association with Martin Sharp and the other editors of Oz magazine during the mid-1960s and Sharp's invitation to him to join The Yellow House at Potts Point; significant artists and performers who had links to the Yellow House in the early 1970s; the influence that the "Yellow House" period had on his career and mentions Brett Whiteley, Donald Friend and others; his portraits of Australian artists and how difficult it is photographing paintings; the contrast between commissioned work and the work of his own choosing.
Recorded on Mar. 8, 2000 at Randwick, NSW.
Digital master available
Weight grew up in Dee Why on the northern beaches of Sydney in the late 1940s to early 1960s, left home and school to work in the Art Dept. of an advertising agency in Sydney. He then made the move into photography as an assistant to Alan Nye at the age of 19 and with some family assistance started operating as an independent photographer in inner Sydney. He recalls buying land in the 1970s near the Hawkesbury River and adopting an alternative lifestyle; teaching photography at Hornsby Technical College; accepting commissions & exhibiting photographs; during the mid-1960s assistant to Martin Sharp (co-editor Oz Magazine); early 1970s invited by Martin Sharpe to join "The Yellow House" at Potts Point, Sydney.
Timed summary and transcript (typescript, 48 leaves) available.
Keywords: Weight, Greg, -- 1946- -- Interviews; Yellow House (Potts Point, N.S.W.); Oz (Sydney, N.S.W.) .; Photographers -- New South Wales -- Interviews; Freelance photography -- New South Wales -- Sydney; Portrait photography -- New South Wales -- Sydney; Photographers